Model Sociopreneurship dalam Pengembangan Produk Kerajinan Tas Kulit Berbasis Ekonomi Kreatif pada Larissa Craft - Elisa Prima Sari; Rahma Talita Syahada; Salma Durrotunnisha; Anik Widiastuti (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
The development of the creative economy in Indonesia shows a positive trend and has become a strategic sector in supporting national economic growth, particularly through job creation and improving community welfare. One subsector with great potential is the leather craft industry, especially leather bags, which have aesthetic value, function, and high competitiveness. This study aims to analyze the sociopreneurship model in the development of creative economy-based leather bag craft products at Larissa Craft and examine the resulting social impact. The study used a descriptive qualitative approach with a purposive sampling technique for determining informants. Data were collected through semi-structured interviews, observation, and documentation, with the researcher as the main instrument (human instrument). Data validity was tested using technical triangulation, while data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results show that Larissa Craft applies a sociopreneurship model by integrating economic and social aspects through local community empowerment, product innovation, and the use of digital technology in marketing. In addition, this business also adopts local wisdom and cultural identity in product design, thereby increasing added value and competitiveness. This model has been proven to be able to create social impacts in the form of increased skills, job creation, and strengthening the community economy. Thus, the application of sociopreneurship at Larissa Craft is an effective strategy in realizing a sustainable, inclusive, and competitive creative economy business.